Pemanfaatan Produksi Sampah Rumah Tangga di TPA Antang Tamangapa Kecamatan Manggala - Marpaung, Mauritz Pandapotan; Jaya, Rachmad; Putri, Safridha Kemala (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Every day waste production is increasing along with the increase in the number of products and people's consumption patterns. As a consequence, the waste problem becomes neglected, as waste management is difficult for the community to control. Maintaining the cleanliness of the living environment is very important by managing waste through the use of existing facilities to reduce the accumulation of waste, especially household waste. For this reason, Community Service activities are held with the aim of providing education as well as building public awareness of the importance of managing waste. As a form of implementation of one of the Tri Dharmas of Higher Education. The method used is counseling about waste as well as education about how to manage waste by utilizing existing facilities and also simulating waste sorting by participants. As a result of implementing this PKM activity, the community can implement good and correct waste management in their daily lives and can take advantage of existing waste management facilities around where the community lives.